ANALYSIS OF REINFORCEMENT OF HIGHWAY BRIDGE FLOOR SLABS WITH STEEL PLATE BONDING METHOD - Gali Pribadi (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Toll Road experienced structural fractures in almost all bridge floor plates. The purpose of this paper is to identify and measure the crack depth with a Portable Ultrasonic Non Destructive Digital Indicating Tester tool, then determine the required strengthening model by calculating deflection on the bridge floor plate. The research method with direct survey on the bridge that occurred cracking by measuring cracks and applying reinforcement with the Steel Plate Bonding method. To find the deflection and stress on the bridge element, the load test is carried out before and after reinforcement. The results showed that steel plate bonding reinforcement on the concrete floor structure could reduce the deflection that occurred at 157.95-420.00% from the initial deflection and reduce the reinforcement stress by 181.82% - 267.74%.